2021
DOI: 10.1088/1748-605x/abc7f2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cefazolin-containing niosome nanoparticles against methicillin-resistant Staphylococcus aureus biofilm formed on chronic wounds

Abstract: The ability of biofilm formation in methicillin-resistant Staphylococcus aureus (MRSA) causes significant mortality and morbidity in wound infections. Nanoparticles because of the drug concentration increment at the point of contact of nanoparticles and bacteria, and slower release of the drug at the desired location are considered as proper tools to overcome the therapeutic problem of antimicrobial-resistant infections. This study was aimed to evaluate the anti-biofilm activity of cefazolin-loaded nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…According to the acquired results, after 48 h of monitoring the drug release, the concentration reached more than half. Our previous study had also revealed that these NPs eradicated methicillin‐resistant Staphylococcus aureus biofilms isolated from the patients' ulcers 23 …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…According to the acquired results, after 48 h of monitoring the drug release, the concentration reached more than half. Our previous study had also revealed that these NPs eradicated methicillin‐resistant Staphylococcus aureus biofilms isolated from the patients' ulcers 23 …”
Section: Discussionmentioning
confidence: 92%
“…The final solid film was then dried entirely using nitrogen gas and suspended in 20 ml of 1 M phosphate buffer saline (PBS) with a pH value of 7.4, at 60°C (Figure 1). All prepared batches were visually observed for turbidity and flocculation in transparent containers at 4°C 23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2014) and S. aureus isolates from both diabetic foot and pressure ulcers (Pasteur Institute of Iran) (Zafari et al . 2020). Three different concentrations of the synthetic compounds (stock concentration of 1000 µg ml −1 ; test concentrations of 40, 20 and 10 µg ml −1 in acetone) were poured on each disc (6·4 mm diameter, Padtan Teb co.).…”
Section: Methodsmentioning
confidence: 99%